Solomonsterol A, a Marine Pregnane-X-Receptor Agonist, Attenuates Inflammation and Immune Dysfunction in a Mouse Model of Arthritis - Andrea Mencarelli; Claudio D'Amore; Barbara Renga; Sabrina Cipriani; Adriana Carino; Valentina Sepe; Elisa Perissutti; Maria Valeria D'Auria; Angela Zampella; Eleonora Distrutti; Stefano Fiorucci (Marine Drugs, 2013)
In the present study we provide evidence that solomonsterol A, a selective pregnane X receptor (PXR) agonist isolated from the marine sponge Theonella swinhoei, exerts anti-inflammatory activity and attenuates systemic inflammation and immune dysfunction in a mouse model of rheumatoid arthritis. Solomonsterol A was effective in protecting against the development of arthritis induced by injecting transgenic mice harboring a humanized PXR, with anti-collagen antibodies (CAIA) with beneficial effects on joint histopathology and local inflammatory response reducing the expression of inflammatory markers (TNFα, IFNγ and IL-17 and chemokines MIP1α and RANTES) in draining lymph nodes. Solomonsterol A rescued mice from systemic inflammation were assessed by measuring arthritis score, CRP and cytokines in the blood. In summary, the present study provides a molecular basis for the regulation of systemic local and systemic immunity by PXR agonists.